Design zero-voltage switching DC-DC buck converter - Abdullah, Rohafiza (2014)
This report proposes an integrated, high switching frequency, zero-voltage-switching dc-dc buck converter for battery charger application. The design and analysis of dcdc buck converter with integrated inductor is presented. The converter has been optimized to convert 12V input voltage to 5V at 1.5A maximum load current at 50MHz switching frequency. The converter has been simulated using an ORCAD 16.5 based simulation tool and result show that the switching losses using zerovoltage-switching technique is less compared to conventional buck converter.